Forming characteristics of artificial aging Al-Mg-Si-Cu sheet alloys - Klos, Artur; Kellner, Sven; Wortberg, Daniel; Walter, Philipp; Bassi, Corrado; Merklein, Marion (AIP Conference Proceedings, 2017)
AA6111 is a commonly used aluminum alloy for body-in-white (BIW) components with good bake-hardening response, high strength and excellent formability. For industrial applications various process strategies are considered to reach strength of about 250 MPa in the final body part with that type of alloy. The purpose of this paper is to discuss recent process strategies of high-strength AA6111 sheets to evaluate the forming characteristics, precipitation kinetics dissolution and mechanical properties in the final condition. The forming behavior is investigated by four potential process chains after single-stage or multi-stage heat treatment including T4 (pre-aged at > 80 °C after quenching), T61 (T4 + artificial aged at 120-150 °C for 10-18 h), T6 (T4 + artificial aged at 180-220°C up to 12 h) and PFHT (T4 + post form heat treatment at 205°C for 30 min). The experimental input for characterization of the formability consists of tensile tests, bending tests and drawing tests. Differential Scanning Calorimetry (DSC) is used, to correlate the forming behavior with the precipitation distribution in the advanced stages of aging. The study shows that the forming behavior is strongly dependent on the condition the alloy.
CRIS-Team Scopus Importer:2023-03-29